2011
DOI: 10.1128/mmbr.00028-10
|View full text |Cite
|
Sign up to set email alerts
|

A Guide to the Natural History of Freshwater Lake Bacteria

Abstract: SUMMARY Freshwater bacteria are at the hub of biogeochemical cycles and control water quality in lakes. Despite this, little is known about the identity and ecology of functionally significant lake bacteria. Molecular studies have identified many abundant lake bacteria, but there is a large variation in the taxonomic or phylogenetic breadths among the methods used for this exploration. Because of this, an inconsistent and overlapping naming structure has developed for freshwater bacteria, creating a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

132
1,483
7
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,316 publications
(1,633 citation statements)
references
References 243 publications
132
1,483
7
11
Order By: Relevance
“…Consistent with the presence of this taxon in the eutrophic Yanga Lake (Kobayashi et al, 2013), an analysis of the literature, demonstrating that the abundance of alfV-A can be linked to increased surface water temperatures and high nutrient concentrations, concluded that there was clear evidence that functional heterogeneity occurs within this lineage (Newton et al, 2011). A caveat to this is that the absolute abundance of alfV is overwhelmingly dependent on water turbidity, with phytoplankton blooms drastically decreasing its abundance (Salcher et al, 2011) in a manner akin to that observed in this study.…”
Section: Eubacterial Diversity and Compositionmentioning
confidence: 55%
See 1 more Smart Citation
“…Consistent with the presence of this taxon in the eutrophic Yanga Lake (Kobayashi et al, 2013), an analysis of the literature, demonstrating that the abundance of alfV-A can be linked to increased surface water temperatures and high nutrient concentrations, concluded that there was clear evidence that functional heterogeneity occurs within this lineage (Newton et al, 2011). A caveat to this is that the absolute abundance of alfV is overwhelmingly dependent on water turbidity, with phytoplankton blooms drastically decreasing its abundance (Salcher et al, 2011) in a manner akin to that observed in this study.…”
Section: Eubacterial Diversity and Compositionmentioning
confidence: 55%
“…Freshwater microbial communities exhibit high compositional and functional variability across spatial and temporal scales (Newton et al, 2011), reflecting changes in water chemistry and nutrient concentrations (Allgaier et al, 2007;Newton et al, 2007;Dennis et al, 2013), hydrodynamic stability of the water column (Salcher et al, 2011) and climatological impacts . Periods of high cyanobacterial biovolume are associated with elevated rates of denitrification (McCarthy et al, 2007) and carbon sequestration (Becker et al, 2011;Sandrini et al, 2014), applying additional perturbations to the water column that in turn contribute to already highly variable systems .…”
Section: Introductionmentioning
confidence: 99%
“…The well-known freshwater planktonic bacteria (e.g. Synechococcus, Limnohabitans, ‗Candidatus Limnoluna', ‗Candidatus Planktophila', other actinobacterial genera, members of Flavobacteria and the LD12 group of the SAR11 clade; Hahn, 2009;Jezbera et al, 2009;Felföldi et al, 2011;Newton et al, 2011;Kasalický et al, 2013;Pernthaler, 2013) were abundant in the water of Lake Balaton, but were nearly absent in the intestine samples. One possible explanation for this phenomenon is that members of the bacterioplankton are not or just partially filtered out from the water, since their cells are usually smaller than 10 µm (a filtration-size threshold proposed for bigheaded carps by Vörös et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Community Composition at a High Taxonomic Level Due to the strong vertical chemical gradients and zonation of redox reactions with depth, a clear vertical stratification of microbial communities is usually observed for meromictic lakes [48][49][50][51]. In spite of the different extraction protocols used, the relative abundances of potentially active and bulk bacterial and archaeal communities were mostly similar at the phylum level, with some notable exceptions.…”
Section: Discussionmentioning
confidence: 99%